Analisis Komparasi Tingkat Kesehatan dan Gejala Financial Distress pada Bank Umum Syariah Indonesia dan Malaysia Periode 2018-2022 - Avisha Yustikasari; Muhtadin Amri (Institut Agama Islam Negeri Ponorogo, 2025)
Introduction: This research aims to analyze the level of bank health and symptoms of financial distress in Indonesian and Malaysian Sharia Banks for 2018-2022 period. Research Methods: The research method is quantitative descriptive using RGEC, Springate S-Score and Zmijewski X-Score. Data analysis using Normality Test, Sign-Wilcoxon Difference Test and Mann Whitney Test. Data used is from the bank's annual financial and GCG report for the 2018-2022 period. Results: Level of bank health using RGEC analysis shows Indonesian Sharia Commercial Banks in